Pertumbuhan Planlet Dendrobium ‘Linda Febriana’ × ‘Nindii’ secara In Vitro pada Berbagai Konsentrasi BAP dan NAA dalam Media Subkultur - Intan Triani; Lisa Erfa; Sekar Utami Putri; Dila Febria (Politeknik Negeri Lampung, 2026)
Orchid propagation through in vitro techniques takes 9-12 months. Culture media plays a very important role in supporting the growth and development of explants. In addition to macro and micro nutrients, sugar, and vitamins, the use of plant growth regulators (PGRs) is needed to accelerate the growth of explants. The objectives of this study were: (a) to obtain the best BAP concentration for the growth of orchid seedlings, (b) to obtain the best NAA concentration for the growth of orchid seedlings, (c) to determine whether there is an interaction between the administration of BAP and NAA concentrations on the growth of orchid seedlings, and (d) to obtain the best combination of BAP and NAA concentrations for the growth of Dendrobium orchids. This study used a 2-factor Randomized Block Design. The first factor was BAP with levels of 1 mg.l-1 (B1), 2 mg.l-1 (B2), and 3 mg.l-1 (B3). While the second factor was NAA with levels of 1 mg.l-1 (N1), 2 mg.l-1 (N2), and 3 mg.l-1 (N3). Observation parameters include increase in seedling height, increase in number of leaves, increase in number of roots, shoot height, and number of shoots. Observation data were analyzed for variance and continued with BNJ test at 5% level. The results of this study indicate that: (a) the best BAP concentration on increasing seedling height, increasing number of leaves, and increasing number of roots is BAP 1 mg.l-1, while on the variable shoot height and number of shoots is BAP concentration 2 mg.l-1, (b) The best NAA concentration is 2 mg.l-1 on increasing seedling height, increasing number of leaves, and increasing number of roots, (c) there is an interaction between BAP and NAA concentrations on increasing seedling height, increasing number of leaves, and increasing number of roots, (d) the best combination of BAP and NAA concentrations is BAP 1 mg.l-1 with NAA 2 mg.l-1 on increasing seedling height, increasing number of leaves, and increasing number of roots.